Guest Editor’s Introduction: AJIC Focus Section on Cybersecurity - Pillay, Kiru (My University, 2017)
This introduction to the AJIC Focus Section on Cybersecurity provides the context for the section, introduces the three articles, and establishes the importance of ongoing emperical research in support of policy and strategy in the cybersecurity domain.
Keywords: cybersecurity, cybersecurity policy, cyber-threats, cybersecurity awareness (CSA), cybersecurity research, developing world, Africa, South Africa